Sulfatase 2 (SULF2) Monoclonal Antibody 5D5 Suppresses Human Cholangiocarcinoma Xenograft Growth Through Regulation of a SULF2–Platelet‐Derived Growth Factor Receptor Beta–Yes‐Associated Protein Signaling Axis. Issue 3 (24th May 2021) - Luo, Xin; Campbell, Nellie A.; He, Li; O'Brien, Daniel R.; Singer, Mark S.; Lemjabbar‐Alaoui, Hassan; Ahn, Keun Soo; Smoot, Rory; Torbenson, Michael S.; Rosen, Steven D.; Roberts, Lewis R.
Abstract : Background and Aims: Existing therapeutic approaches to treat cholangiocarcinoma (CCA) have limited effectiveness, prompting further study to develop therapies for CCA. We report a mechanistic role for the heparan sulfate editing enzyme sulfatase 2 (SULF2) in CCA pathogenesis. Approach and Results: In silico analysis revealed elevated SULF2 expression in human CCA samples, occurring partly through gain of SULF2 copy number. We examined the effects of knockdown or overexpression of SULF2 on tumor growth, chemoresistance, and signaling pathway activity in human CCA cell lines in vitro . Up‐regulation of SULF2 in CCA leads to increased platelet‐derived growth factor receptor beta (PDGFRβ)–Yes‐associated protein (YAP) signaling activity, promoting tumor growth and chemotherapy resistance. To explore the utility of targeting SULF2 in the tumor microenvironment for CCA treatment, we tested an anti‐SULF2 mouse monoclonal antibody, 5D5, in a mouse CCA xenograft model. Targeting SULF2 by monoclonal antibody 5D5 inhibited PDGFRβ–YAP signaling and tumor growth in the mouse xenograft model. Conclusions: These results suggest that SULF2 monoclonal antibody 5D5 or related agents may be potentially promising therapeutic agents in CCA.